Co-resistance to Amoxicillin and Tetracycline as an Indicator of Multidrug Resistance in Escherichia coli Isolates From Animals - Bourély, Clémence; Cazeau, Géraldine; Jarrige, Nathalie; Jouy, Eric; Haenni, Marisa; Lupo, Agnese; Madec, Jean-Yves; Leblond, Agnès; Gay, Emilie (Frontiers in Microbiology, 2019)
Objectives: To examine the relevance of co-resistance to amoxicillin and tetracycline as an indicator of multidrug resistance (MDR) in animal health. Methods: Escherichia coli isolates collected between 2012 and 2016 by the French surveillance network for antimicrobial resistance in diseased animals (RESAPATH) were analysed. The proportions of MDR isolates and the proportions of isolates presenting co-resistance to amoxicillin and tetracycline were calculated for seven animal species (cattle, horse, dog, swine, poultry, duck and turkey). The degree of agreement between these two proportions was estimated by calculating the kappa value. Results: In total, 55,904 isolates were analysed. MDR proportions were variable among animal species, ranging from 21.9% [20.2; 23.7] in horses to 56.0% [55.4; 56.7] in cattle. A similar situation was observed for proportions of isolates with co-resistance to amoxicillin and tetracycline, with the highest value for cattle 65.0% [64.3; 65.6]. This co-resistance was also most often associated with resistance to other antibiotics, regardless of the animal species considered. Comparative analysis showed substantial agreement between MDR and this co-resistance, with a kappa value of 0.75, all animal species considered. Conclusion: Given the widespread use of penicillins and tetracyclines in animal health, co-resistance to amoxicillin and tetracycline can be an efficient indicator of MDR in E. coli isolates. Based on a specific resistance profile and not an arbitrary number of resistances compared with MDR, this potential indicator is also precise, convenient and suitable for routine use.